Effects of Short Wave Diathermy Therapy in Patients with Adhesive Capsulitis of Shoulder (ACS) (Bangladesh Medical Journal, 2023)
There are varieties of management option for Adhesive capsulitis of shoulder (ACS) also known as Periarthrosis and in general population commonly known as Frozen Shoulder. Short Wave Diathermy (SWD) is one of the important therapeutic option for frozen sholder. The aim of the study is to determine effectiveness of SWD in order to improve the pain and range of motion in Adhesive Capsulitis. A total 56 subjects were selected for this non-randomized controlled trial in the Department of Physical Medicine and Rehabilitation, Chattogram Medical College Hospital with adhesive capsulitis in a period of 6 months. The subject were divided into two intervention groups; group-A with conventional treatment plan with SWD and group-B with conventional treatment only. Tool used for assessment were Visual Analogue Scale (VAS) to measure pain with Tenderness Grading (TG) and Shoulder Pain and Disability Index Score (SPADI). The analysis was done to measure the difference of effectiveness of both interventions by independent t-test with SPSS-20. Among 56 patients regarding analysis of sex in both groups male and female were matched (p>0.05) and male - female ratio was 1.66: 1. Considering socioeconomic status, poor was 21.4%, middle class was 44.6% and rich was 33.9%. Among all patients 35.7% were housewives, 16.1% were service holder, farmers were 12.5%, businessmen were 16.2% and laborers were 3.6%. In total patients, 48.2% had right shoulder involvement, 50.0% had left side involvement and one patient had both sided disease. There were 92.7% patients who had localized pain and only 7.3% had radiation. Majority of the experienced pain in the evening was 56.4% and rest had pain at night  was 43.6%. About half of the patients in both groups had constant and intermittent type of pain 47.5% and 45.5% respectively other types were sharp and dull.  Significant difference between Group A and Group B was found at week 2, week 4 and week 6 follow-up (p0.05). Significant difference between Group A and Group B was found at week 2, week 4 and week 6 follow-up (p